Benefit-Cost Analysis of Community Forest and Its Distributional Impact on Rural Poor - Dahal, Mahesh Raj (Economic Journal of Nepal, 2006)
This paper attempts to examine the equity impact of community forest (CF) with the help of cost-benefit analysis among the three income groups of sixteen selected community forest user groups in Arun River Valley, Eastern mid-Hill, Nepal. For the purpose of benefit analysis, eight major types of forest products from CF were incorporated considering as material values and intangible benefits of forest such as environmental service and greenery were overlooked totally. Total costs of forest use and management were classified into labor costs, transaction costs and membership fees. With the help of summary statistics of gross benefits and costs, net benefit and B-C ratios for the three income groups were calculated which showed that the net benefit and B-C ratios of poor, medium and rich households to be -3 and 0.85, 0 and 1, and 4 and 1.08 respectively. The current practices of community forest management have negative impact on rural poor that lacks the provisions for addressing equitable system of benefit distribution and cost sharing among the forest user groups and households. If community forestry is to be rural poor-friendly, poor income households should realize the full value of the share of unused forest products either from transferable rights or from marketable access. Economic Journal of Nepal Vol.29(2) 2006 pp.93-107